Cell type‐selective pathways and clinical associations of lysophosphatidic acid biosynthesis and signaling in the ovarian cancer microenvironment. Issue 2 (15th November 2018) - Reinartz, Silke; Lieber, Sonja; Pesek, Jelena; Brandt, Dominique T.; Asafova, Alina; Finkernagel, Florian; Watzer, Bernard; Nockher, Wolfgang Andreas; Nist, Andrea; Stiewe, Thorsten; Jansen, Julia M.; Wagner, Uwe; et al.
Abstract : The peritoneal fluid of ovarian carcinoma patients promotes cancer cell invasion and metastatic spread with lysophosphatidic acid (LPA) as a potentially crucial mediator. However, the origin of LPA in ascites and the clinical relevance of individual LPA species have not been addressed. Here, we show that the levels of multiple acyl‐LPA species are strongly elevated in ascites versus plasma and are associated with short relapse‐free survival. Data derived from transcriptome and secretome analyses of primary ascite‐derived cells indicate that (a) the major route of LPA synthesis is the consecutive action of a secretory phospholipase A2 (PLA2 ) and autotaxin, (b) that the components of this pathway are coordinately upregulated in ascites, and (c) that CD163+CD206+ tumor‐associated macrophages play an essential role as main producers of PLA2 G7 and autotaxin. The latter conclusion is consistent with mass spectrometry‐based metabolomic analyses of conditioned medium from ascites cells, which showed that tumor‐associated macrophages, but not tumor cells, are able to produce 20:4 acyl‐LPA in lipid‐free medium. Furthermore, our transcriptomic data revealed that LPA receptor ( LPAR ) genes are expressed in a clearly cell type‐selective manner: While tumor cells express predominantly LPAR1‐3, macrophages and T cells also express LPAR5 and LPAR6 at high levels, pointing to cell type‐selective LPA signaling pathways. RNA profiling identified cytokines linked to cell motility and migration as the most conspicuous class of LPA‐induced genes in macrophages, suggesting that LPA exerts protumorigenic properties at least in part via the tumor secretome. Abstract : Lysophosphatidic acid (LPA) in the ovarian cancer microenvironment is produced via phospholipase PLA2 and autotaxin secreted by tumor‐associated macrophages (TAM). After binding to LPAR receptors on tumor cells, LPA induces the production of growth factors and cytokines and triggers matrix invasion, associated with an early disease recurrence in patients.